2000
DOI: 10.1128/jvi.74.1.173-183.2000
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Trout Sleeping Disease Virus Is an Atypical Alphavirus

Abstract: Sleeping disease (SD) is currently a matter of concern for salmonid fish farmers in most parts of the world. A viral etiology of SD has recently been suspected, since virus-like particles have been observed in infected rainbow trout cells. In salmonid-derived cell lines, the maximal rate of virus production was observed at 10°C, while little virus was produced at 14°C. Through biochemical, physicochemical, and morphological studies, SD virus (SDV) was shown to be an enveloped virus of roughly 60 nm in diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
105
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 20 publications
4
105
1
Order By: Relevance
“…However, Hodneland et al (2005) recently showed that pancreas disease from Atlantic salmon and rainbow trout in Norway is in fact caused by a different and distinct virus subtype, and named it Norwegian salmonid alphavirus (NSAV). Together with the sleeping disease virus (SDV) (Boucher and Baudin Laurencin, 1994;Branson, 2002;Castric et al, 1997;Graham et al, 2003b;Villoing et al, 2000a) and salmon pancreas disease virus, the Norwegian salmonid alphavirus is included in the species Salmonid alphavirus in the genus Alphavirus of the family Togaviridae. All three salmonid alphavirus subtypes have a genomic organization characteristic to the Alphaviruses; with a positive-sense, single stranded genome of approximately 11.8 kb size.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hodneland et al (2005) recently showed that pancreas disease from Atlantic salmon and rainbow trout in Norway is in fact caused by a different and distinct virus subtype, and named it Norwegian salmonid alphavirus (NSAV). Together with the sleeping disease virus (SDV) (Boucher and Baudin Laurencin, 1994;Branson, 2002;Castric et al, 1997;Graham et al, 2003b;Villoing et al, 2000a) and salmon pancreas disease virus, the Norwegian salmonid alphavirus is included in the species Salmonid alphavirus in the genus Alphavirus of the family Togaviridae. All three salmonid alphavirus subtypes have a genomic organization characteristic to the Alphaviruses; with a positive-sense, single stranded genome of approximately 11.8 kb size.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, alphaviruses can be cultured in many vertebrate and insect cell lines (11)(12)(13). In contrast, the distantly related fish alphaviruses, which are not known to have arthropod vectors, exhibit a narrow host range (fish cells only) that is at least partially a result of temperature sensitivity (14)(15)(16). However, the viral factor(s) that underlie the varying host range of alphaviruses are poorly understood.…”
mentioning
confidence: 99%
“…The characteristic signs of the disease include the unusual behaviour of fish 'sleeping' on their sides at the bottom of the tank. A viral aetiology of the disease was suspected, as virus-like particles were observed in purified homogenates from the kidneys of diseased fish (1).The virus was first isolated in France (3) and fully characterised as an alphavirus (14). Historically, the disease has been endemic in parts of France with up to 30% of trout farms in Brittany infected (15).…”
Section: Introductionmentioning
confidence: 99%